Scanning electron microscopic study on the oviduct of buffalo during follicular and luteal phases of estrous cycle - PATHAK, DEVENDRA; BANSAL, NEELAM (The Indian Journal of Animal Sciences, 2018)
The present investigation was conducted on different segments of oviduct of six buffaloes each during follicular and luteal phases of estrous cycle. The mucosa of different segments of oviduct was thrown into folds which were oriented as primary and secondary folds. The lamina epithelialis was lined with ciliated and non-ciliated cells. Ciliated cells had many kinocilia during the follicular phase. The non-ciliated cells were of two types, viz. secretory and non-secretory type. The infundibulum during the follicular phase had large number of ciliated cells as compared to that of luteal phase. The secretory cells had short, thick and stubby microvillous processes. The ampulla had almost similar ciliation as that of infundibulum. The luminal surface of secretory cells had secretory blebs and secretory material over it. The extent of ciliation decreased towards the uterotubal junction. The ciliated cells were more during the follicular phase as compared to that of the luteal phase.